Measuring research and development expenditures in the U.S. economy interim report ; Panel on Research and Development Statisstics at the National Science Foundation, Committee on National Statistics, Division of Behavioral and Social Sciences and Education, National Research Council of the National Academies - Brown, Lawrence D.; Plewes, Thomas J.; Gerstein, Marisa A.; ebrary, Inc. (Washington, DC : National Academies Press, 2005)
Panel to Review Research and Development Statistics at the National Science Foundation. The panel was convened in January 2002 by the Committee on National Statistics of the National Academies at the request of the National Science Foundation to conduct an in-depth and broad-based study of the Research and Development Statistics program of the NSF Science Resources Statistics (SRS) Division. The study was later mandated by Congress in the National Science Foundation Authorization Act of 2002.
Electronic reproduction.
Keywords: Scientific surveys -- United States; Science and industry -- United States; Research, Industrial -- United States; Research -- Economic aspects -- United States; Research, Industrial -- Economic aspects -- United States; Science and industry -- Government policy -- United States; Research, Industrial -- Government policy -- United States; Electronic books